Determinants of Voting Behavior in Khyber Pakhtunkhwa: A Case Study of General Elections in 2002 - Safi Ullah Khan Marwat , Taseer Ullah Khattak (JSSH, 2024)
This research paper analyzes the determinants of voting behavior in Khyber Pakhtunkhwa (KP) during the General Elections in 2002. In electoral politics, apprehension of voting behavior at the macro-level (national) has significance, but understanding it at micro-level (provincial) is also of great value. The main themes of this research are to determine the factors that significantly affected the public choice to vote and to explore the factors that are accountable for the province’s political association. A sample size of 800 respondents was selected using a multistage and systematic method of sampling. It is argued that social determinants (51%) are more important than political (39.9%) and economic (6.5%) determinants in defining the voting behaviour in KP during General Elections of 2002. In this research, the value of the Pearson Chi-Square test provided a significant Probability Value (P-Value) that shows strong correlation among the several variables like area, age, gender, literacy, profession and monthly income stratifications.